Association between Vertebral Artery Hypoplasia and Vertebral Artery Aneurysms: A Case-Control Study - Harati, Ali; Zeh, Dominik; Rohde, Stefan; Schultheiß, Rolf; Schmieder, Kirsten; Hernesniemi, Juha (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background The aim of this retrospective case-control study was to determine the association of vertebral artery hypoplasia (VAH) and other anatomical variants with saccular vertebral artery posterior inferior cerebellar artery (VA-PICA) aneurysms.Methods The frequency of VAH, vertebral artery (VA) atresia, VA aplasia, and PICA aplasia was analyzed using computed tomography (CT) angiography in 64 patients with VA-PICA aneurysms (43 ruptured and 21 unruptured) and compared with 128 age- and sex-matched controls. Logistic regression was performed to identify independent risk factors for aneurysm formation.Results Univariate analysis showed that patients with VA-PICA aneurysms had a significantly higher frequency of VAH (53% versus 17%; odds ratio [OR] 4.8; 95% confidence interval [CI], 2.4–9.4; p < 0.0001) and VA aplasia (14% versus 1%; OR 20.8; 95% CI, 2.5–168.0; p = 0.004) compared with controls. VA-PICA aneurysms are detected significantly more often in the dominant VA, which is contralateral to VAH. Other anatomical variants are not related to aneurysm formation.Conclusions VAH and VA aplasia are potential risk factors for VA-PICA aneurysms. Altered hemodynamics caused by VAH may result in intracranial aneurysm formation. Additional research should clarify the pathophysiologic association of VAH, VA aplasia, or vascular occlusion with arteriosclerosis and intracranial aneurysm formation.
Keywords: computed tomography angiography; intracranial aneurysm; posterior inferior cerebellar artery; vertebral artery; vertebral artery hypoplasia; posterior circulation